The influence of fibronectin on proliferation and apoptosis of acute lymphoblastic leukaemia cells in vitro - Włodek, Joanna; Pituch-Noworolska, Anna (Polish Journal of Pathology, 2018)
The extracellular matrix (ECM) is a dynamic environment involved in the regulation of haematopoiesis. A crucial role of this structure is the promotion of proliferation, maturation, and differentiation of haematopoietic stem cells (HSC), and adhesion and migration of HSC in bone marrow. In the present study the effect of ECM proteins (fibronectin, collagens, laminin, thrombospondin, and vitronectin) on proliferation and apoptosis of acute lymphoblastic leukaemia cells isolated from acute lymphoblastic leukaemia (ALL) patients ( in vitro ) was assessed. The leukaemia cells were obtained as interphase on Ficoll/Isopaque (Pancoll human, PAN-Biotech) density gradient and, after washing, counted in a chamber. Subsequently, cells were used for culture and apoptosis assay. Presence of fibronectin, collagen type IV, and laminin was associated with inhibition of lymphoblastic leukaemia cell proliferation. Analysis of the culture of lymphoblastic leukaemia cells in the presence of ECM showed fibronectin as the most active protein.